CHEMICAL ANALYSIS OF MACROPHYTE (CYPERUSALTERNIFOLIUS) GROWING IN SURFACE FLOW CONSTRUCTED WETLAND (SFCW) FOR WASTEWATER TREATMENT - Hadidi, Luna Al; Sweity, Amer (International Journal of Research -GRANTHAALAYAH, 2022)
We examined the chemical contents of Cyperusalternifolius growing in surface flow constructed wetlands (SFCW) used in the treatment of partially treated wastewater. The (SFCW) wetland is composed of three cells in series of which two are open water surfaces and one is a channel bed planted with Cyperusalternifolius was designed and constructed. Four different mixtures of treated wastewater TWW effluent and the primary TWW effluent were used under different hydraulic retention times (HRT) of 3, 6, 9, and 12 days within the (SFCW) wetland. Higher accumulation of nitrogen N was detected in the plant’s parts in an order magnitude of leaves>stem>rhizome>root. Pronounced increase in potassium K concentration at the rhizome and stem was detected, while high amount of manganese Mn was accumulated in leaves. Roots and rhizomes were the main sinks for zinc Zn and phosphorus P